Juden und Nichtjuden nach der Shoah : Begegnungen in Deutschland - Fischer, Stefanie HerausgeberIn; Riemer, Nathanael HerausgeberIn; Schüler-Springorum, Stefanie 1962- HerausgeberIn (Europäisch-jüdische Studien – Beiträge, 2019)
Given what we know about Nazi crimes of violence, it is hard for us to imagine encounters between Jews and non-Jews after 1945. Yet many connections developed between Holocaust survivors, refugees, hangers-on, observers, and profiteers. The volume examines relationships in civil society between Jewish and non-Jewish Germans from a historical and cultural historical perspective